Fasting Versus Post-Challenge Triglycerides and Pre-Existing Cavitating Lacunes: A Berlin “Cream & Sugar” Substudy - Leonards, Christopher O.; Wang, Li; Fiebach, Jochen B.; Endres, Matthias; Ebinger, Martin (Frontiers in Neurology, 2013)
Background and Purpose: Although the presence of cavitating lacunes on brain imaging may have prognostic implications, the modifiable risk factors underlying these frequently observed lesions are not completely understood. We sought to determine if fasting and post-challenge triglycerides associate with cavitating lacunes. Methods: All first ischemic stroke patients who completed a novel combined oral triglyceride and glucose tolerance test and MRI between January 2009 and June 2012 were included. Fluid-attenuated inversion recovery or T2 MRI sequences were used to visualize cavitating lacunes and white matter hyperintensities, which were graded using the Wahlund visual scale. Results: 190 patients were included (median age 66, IQR 52-73; 33% female; median National Institute of Health Stroke Scale 2, IQR 1-4). A forward stepwise binary logistical regression analysis applying the Hosmer-Lameshow goodness of fit test adjusted for parameters significant in univariate analyses (at the p<0.10 level) revealed that Wahlund scores (Wahlund 0-4: reference; Wahlund 5-10: adjusted odds ratio, 5.1; 95% confidence interval, 1.3-20.0, P=0.019; Wahlund >10: adjusted odds ratio 9.6; 95% CI, 1.55-59.35; P=0.015) and the highest quartile of post-challenge triglycerides (>295 mg/dL; adjusted odds ratio, 7.36; 95% confidence interval 1.24-43.70; P=0.028) independently associated with the presence of cavitating lacunes. Conclusion: Post-challenge serum triglycerides are independently associated with the presence of cavitating lacunes. Clinical Trial Registration Information: The Berlin “Cream&Sugar” study is registered with EudraCT (2009-010356-97) and clinicaltrials.gov (NCT 01378468).